Digital Marketing in the Function of Sales on the Marketplace - Prdić, Nedeljko; Kostić, Sara (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
Digital marketing includes marketing activities that use the Internet or electronic devices to reach consumers in the modern technological era. Digital marketing provides interaction with customers and business partners using digital information technologies and electronic means. The Covid-19 pandemic undoubtedly had a negative impact on both the world and local economy, and as a result, economic activity fell due to the closure of the economy. In this regard, Covid-19 has had a great impact in all areas of human life and work, the need for digital transformation of economic entities has been significantly accelerated. Covid-19 influenced the change in the way the marketplaces work as an extremely important channel for the distribution of food products. The aim of this paper is to analyse the market position of marketplaces during the pandemic and to establish intensive and interactive communications between sellers based on consumer needs. The research is based on the application of special methods of knowledge and marketing research methods that are adapted to the needs of the problem. Amongst the special methods of cognition, the methods of analysis and synthesis, logical deduction and statistical data processing are used. The theoretical assumption of the research is based on the analysis of existing literature, authors’ experience and available data on the Internet in the field of marketing and digital marketing. The test method was used to collect and analyse qualitative data and information. A survey questionnaire was used to investigate the fears of sellers in the three marketplaces in question after the resumption of work due to the pandemic. Also, the research covers the attitudes of consumers after the start of the marketplace. The results of the research provided a reliable basis for drawing conclusions, that the sellers do not have an adequate database of customers and that they have insufficiently used the existing electronic sales channels of ePijaca. The sellers to a certain extent made contact with consumers through the social networks Facebook and Instagram. Consumer attitudes indicate that they lacked marketplaces as a channel for supplying agricultural products. The conclusion is that based on the attitudes of marketing research of sellers and consumers, the efficiency of communication through digital marketing can be increased, all with the aim of achieving economic effects.